2020
DOI: 10.48084/etasr.3317
|View full text |Cite
|
Sign up to set email alerts
|

Openings Effect on the Performance of Reinforced Concrete Beams Loaded in Bending and Shear

Abstract: Transverse openings are often provided to reinforced concrete beams to accommodate utility ducts and pipes. This technique is usually adopted to avoid the creation of dead space in structures caused by extended dropped ceilings and leads to significant cost saving. On the other hand, the provision of openings through a beam creates a reduction in its strength and affects serviceability. In this study, ten reinforced concrete beams were cast using C30 concrete. Material characterization and engineering properti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 4 publications
0
6
0
1
Order By: Relevance
“…The shear capacity in the normal beam is limited to an opening height of less than 0.25 of the overall beam depth [ 45 , 46 ]. However, in a deep beam, both the height and length of the opening influence the load capacity of the section.…”
Section: Methodsmentioning
confidence: 99%
“…The shear capacity in the normal beam is limited to an opening height of less than 0.25 of the overall beam depth [ 45 , 46 ]. However, in a deep beam, both the height and length of the opening influence the load capacity of the section.…”
Section: Methodsmentioning
confidence: 99%
“…In recent years, for an RC residential building structure, designers have frequently encountered the problem of a transverse opening in the plastic hinge region of a beam member due to actual pipeline configuration requirements. Recent studies have been conducted on the behavior of simply supported RC beams with transverse opening (Ame et al, 2020;Amiri et al, 2011;Chiu et al, 2023;Ling et al, 2020), some researchers have also reported the use of FRP to strengthen the transverse opening region (Aksoylu et al, 2020;Morsya and Barima, 2019;Özkılıç et al, 2022). However, very little research on a transverse opening in the plastic hinge region of an RC beam has been performed.…”
Section: Introductionmentioning
confidence: 99%
“…In practice, a network of ducts and pipes is needed to accommodate utilities like sewage, power, air conditioning, telephone, and water supply [1]. Accordingly, most of the Reinforced Concrete (RC) structures in Iraq contain holes in RC beams, commonly known as penetrations or openings, which are created to accommodate the passage of piping or other utilities [2].…”
Section: Introductionmentioning
confidence: 99%